Feasibility of combining tDCS with exercise for increasing physical activity in people with depression - Abrantes, Ana M.; Browne, Julia; van ‘t Wout-Frank, Mascha; Carpenter, Linda L.; Stein, Michael D.; Uebelacker, Lisa A.; Audet, Daniel; Desaulniers, Julie A.; Garnaat, Sarah (Frontiers in Physiology, 2025)
IntroductionPhysical inactivity and depression are significant public health concerns, often co-occurring and exacerbating one another. Transcranial direct current stimulation (tDCS) has shown promise in enhancing cognitive and affective processes, potentially improving exercise adherence and outcomes in individuals with depressive symptoms. This study aimed to evaluate the feasibility and preliminary within group effects of combining tDCS with an aerobic exercise (AE) intervention to increase physical activity in individuals with elevated depressive symptoms.MethodA pilot randomized controlled trial (RCT) was conducted with 51 participants exhibiting low physical activity levels and elevated depressive symptoms. Participants were randomized to receive either active tDCS (n = 25) targeting the left dorsolateral prefrontal cortex (DLPFC) or sham tDCS (n = 26), followed by supervised AE sessions three times per week for eight weeks. Physical activity was measured using accelerometers, and secondary outcomes included cardiorespiratory fitness, depressive symptoms, and affect.ResultsFeasibility metrics indicated moderate adherence rates to sessions, good follow-up rates, and successful blinding as belief about receiving active stimulation was comparable across conditions. Within the active tDCS group, small-to-medium effect sizes were observed for increases in accelerometer-derived daily steps (d = 0.36) and MVPA (d = 0.34) at end of treatment. Both the active tDCS and sham groups demonstrated large within-group improvements in cardiorespiratory fitness (d = 0.99 for active, d = 1.18 for sham) and self-reported MVPA (active d = 0.78, sham d = 0.90). Similarly, large reductions in depressive symptoms (active d = −1.00, sham d = −0.88) were observed within both groups.DiscussionThe combination of tDCS and AE appears feasible and shows preliminary potential for positively influencing daily step counts in individuals with depressive symptoms. The results support further investigation into tDCS as an adjunctive treatment to enhance exercise outcomes in this population.